Amyloid arthropathy associated with multiple myeloma: polyarthritis without synovial infiltration of CD20+ or CD38+ cells. (March 2014) - Pessler, Frank; Ogdie, Alexis R.; Mayer, Christian T.; Kretzschmar, Warren W.; Dai, Lie; Elsaman, Ahmed M.; Einhorn, Eugene; Krenn, Veit; Schumacher, H. Ralph
Abstract Objectives: To describe histological, immunohistochemical and ultrastructural features of synovial biopsies of amyloid arthropathy associated with multiple myeloma (MM). Methods: Synovial biopsies from affected joints of two patients with MM and amyloid arthropathy were examined with light and electron microscopy, and immunohistochemically for expression of CD3, CD8, CD20, CD38, CD68, Ki-67 and vWF. Results were compared to values from osteoarthritis (OA, n = 26), rheumatoid arthritis (RA, n = 24) and normal (n = 15) synovial membranes. Results: There was no or only mild lining hyperplasia. Vascular density was not elevated, and there were few Ki-67+ proliferating cells in the stroma. The Krenn synovitis score classified one specimen as "low-grade" and one as "high-grade" synovitis. CD68+ and CD3+ cells were the predominant mononuclear inflammatory cells, whereas CD20+ and CD38+ cells were absent from both synovial membrane and synovial fluid sediment. Electron microscopy demonstrated amyloid phagocytosis by synovial macrophages. In hierarchical clustering the two amyloid arthropathy specimens were more closely related to OA than to RA or normal synovium. Conclusions: This first detailed immunohistological analysis of MM-associated amyloid arthropathy suggests that it is a chronic synovitis that evolves despite the loss of humoral immunity seen in advanced MM. Instead, amyloid phagocytosis by synovial macrophages likely triggers and perpetuates local disease.